320 A Closed Loop Audit of Surgical Site Infection Rate in Elective Colorectal Laparotomies, Pre and Post Introduction of Jubilee Dressing Method. (4th May 2021) - Denton, O; Knight, K; Steele, C
Abstract: Introduction: Surgical site infections (SSI) are responsible for one third of all inpatient infections and are associated with increased morbidity and extended hospital stay. The colorectal department at Glasgow Royal Infirmary introduced the Jubilee dressing method in August 2019 with the aim of reducing SSI incidence. Method: Closed loop audit of all elective colorectal laparotomies at Glasgow Royal Infirmary pre- and post-introduction of Jubilee dressing method (March – July & August – December 2019). Literature reviews informed selection of baseline characteristics relevant to SSI. Analysis by logistic regression of SSI incidence by characteristic and Jubilee dressing use. Results: A total of 193 patients were included. There was 52% uptake of Jubilee dressing method in the implementation phase and reduction in total SSI rate from 18.25% to 14.93%. Operation duration and smoking history were the only significant factors at univariate analysis and were put forward to multivariate analysis. Of these, only operation duration made a significant contribution to SSI incidence. Conclusions: Jubilee dressing use did not make a significant difference to SSI incidence in this sample. This intervention is likely to have small effect size and there were probable confounding factors. Multifactorial influence in SSI incidence suggests larger datasets are required to isolate independent factors.